Effect of 3 types of antifungal agents on hardness of 2 different commercially available tissue conditioners: An in-vitro study - Vijeta Jadhav; M Mitha Shetty; N Kalavathy; Roshan Kumar (Wolters Kluwer Medknow Publications, 2013)
Objectives: The primary objective of the following study is to evaluate and secondary objective is to compare the hardness of two different tissue conditioners before and after the addition of three types of antifungal agents. Materials and Methods: Two types of tissue conditioners: viscogel and coe-soft were manipulated with three types of antifungal agents (fluconazole, clotrimazole, neem) and placed in the metal mold as per the manufacturer's instructions. A total of 240 samples were fabricated and divided into two groups of 120 samples each and were grouped as, T1 - Viscogel., T2 - Coe-soft. These were subjected to hardness test on 1 st , 7 th 14 th days with the Shore-A-Durometer equipment. Results: Tissue conditioners showed an increase in hardness values with the use of antifungal agents in all the groups. Conclusion: The study can be concluded that hardness of Viscogel was statistically significant when mixed with fluconazole and compared with coe-soft as on 1 st day, 7 th day and 14 th day.